Public health policies for the private population of liberty: a case study - Vecchia, Bruno Dalla Vendramini; dos Santos, Gabriel Advincula; Esteves, Giovana Abram Pelodan; Lopes, Joao Lucas; Conception, Luiza Sabadini Conception; Thomé, Pedro Henrique Fernandes; Reis, Rangel Silva; Eni, Sarah Eko; de Sousa, Rosa Gouvêa (Seven Editora, 2023)
The municipality of São João del-Rei is located in the State of Minas Gerais, being part of the mesoregion of Campo das Vertentes. Its territorial area borders the municipalities of Santa Cruz de Minas, Tiradentes, Coronel Xavier Chaves, Ritápolis, Prados, Barroso, Conceição da Barra de Minas, Nazareno, Madre de Deus de Minas, Piedade do Rio Grande (IBGE, 2021). According to the latest ibge data (2021), São João Del Rei has a population of approximately 90,000 people, thus presenting a population density of 57.68 inhabitants/km². DOI: https://doi.org/10.56238/colleinternhealthscienv1-085